Hubungan Konsumsi Kafein Dengan Kejadian Gastritis pada Remaja SMAN 6 Kabupaten Tangerang - wahyu anugrah wardhana wahyu (Jurnal Riset Media Keperawatan, 2026)
Background: Gastritis is one of the most common digestive health problems among adolescents and is closely related to caffeine consumption patterns. Caffeine contained in coffee, tea, chocolate, and energy drinks is known to increase gastric acid production, which may irritate the gastric mucosa. The increasing trend of caffeine consumption among adolescents raises concern as it may contribute to a higher risk of gastritis. Objective: To determine the relationship between caffeine consumption and the incidence of gastritis among adolescents at SMA Negeri 6 Kabupaten Tangerang. Method: This study employed an analytic quantitative design with a cross-sectional approach. The population consisted of all 12th-grade students with a total of 120 respondents, selected using a purposive sampling technique. The research instruments were a caffeine consumption questionnaire and a gastritis questionnaire. Data were analyzed using univariate and bivariate analyses with Spearman’s rho correlation test. Results: The findings showed that the majority of respondents had a high level of caffeine consumption (66.7%), and 55.4% of respondents were at risk of developing gastritis. The bivariate analysis revealed a correlation coefficient of r = 0.806 with p-value < 0.001, indicating a very strong and significant positive relationship between caffeine consumption and the incidence of gastritis among adolescents. Conclusion: There is a very strong relationship between caffeine consumption and the incidence of gastritis among adolescents at SMA Negeri 6 Kabupaten Tangerang. The higher the level of caffeine consumption, the greater the risk of gastritis. Recommendation: This study is expected to serve as a basis for health education among adolescents and schools to help control caffeine consumption patterns and maintain them within safe limits. Keywords: Caffeine consumption, Gastritis, Adolescents